2022
DOI: 10.3389/fpls.2022.849010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of South-to-North Water Diversion Project Cascade Dams on Riparian Vegetation Along the Middle and Lower Reaches of the Hanjiang River, China

Abstract: The influence of the construction of dams for water diversion on the ecological environment has attracted recent widespread attention. Over time, dams have emerged as one of the most important factors affecting the vegetation along the riparian zones of rivers. To elucidate the effects of cascade dams on riparian vegetation along the middle and lower reaches of the Hanjiang River, we examined riparian vegetation types upstream and downstream from dams. A total of 14 sample sites and 131 quadrats perpendicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Litter decomposition is considered the more important control factor. It has been shown that invasive plants decompose more rapidly due to their nitrogen-rich nature (Gao et al, 2016 ; Yang et al, 2022 ). While climate and environmental change caused the exotic species to invade, the variances in growth traits between exotic and native plants led to the invasive plant's entry into the plant community, altering the mean plant community traits, which may impact the litter decomposition rates (Ashton et al, 2005 ; Leffler et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Litter decomposition is considered the more important control factor. It has been shown that invasive plants decompose more rapidly due to their nitrogen-rich nature (Gao et al, 2016 ; Yang et al, 2022 ). While climate and environmental change caused the exotic species to invade, the variances in growth traits between exotic and native plants led to the invasive plant's entry into the plant community, altering the mean plant community traits, which may impact the litter decomposition rates (Ashton et al, 2005 ; Leffler et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Floodplain forests, as an important component of riparian ecosystems, are crucial for maintaining these functions and services of the ecosystem [3,8]. However, riparian ecosystem functions and their services have suffered significant negative impacts with the damming of rivers on a global scale [11,12]. Beyond this threat, riparian areas are currently threatened by agricultural practices, industrialization, changes in river flows, climate change, pollution, and biological invasions [10,13].…”
Section: Introductionmentioning
confidence: 99%